Coronary stent embolism to the right posterior cerebral artery - Sinan Varol; İrfan Şahin; Gökmen Kum; Fahrettin Katkat; Ertuğrul Okuyan (KARE Publishing, 2020)
A 57-year-old male was admitted to the emergency room with chest pain that has been present for 3 hours. His blood pressure was 70/50 mmHg and heart rate was 48 bpm. 12-lead surface electrocardiography revealed inferior myocardial infarction and third-degree atrioventricular (AV) block. An emergency coronary angiography showed a 50% stenosis in the middle segment of the left anterior descending artery and 90% in the proximal circumflex (Cx) artery. The right coronary artery was totally occluded. After the predilatation with a 2.0x15 mm compliant balloon at 10 atm, a 3.5x24 mm bare metal stent was implanted. The third-degree AV block improved and a sinus rhythm of 124 bpm was achieved, but hemodynamic stability was not attained. Percutaneous coronary intervention for the Cx artery was performed. Without predilatation, a 3.5x12 mm low profile BMS was easily advanced over the lesion. Just before the stent implantation, asystole developed, followed by convulsions. Blood pressure and heart rate recovered after the administration of 1 mg of atropine. However, during the seizure, the guidewire and coronary stent device fell to the aortic root. Stent struts were not seen on the balloon catheter in a fluoroscopic examination. Fluoroscopic scanning of the vascular system showed that the coronary stent was in the right posterior cerebral artery. There were no symptoms or signs of neurological disorder. Consultant invasive neuroradiologist recommended medical follow-up. Clopidogrel and acetylsalicylic acid were prescribed indefinitely. Two months after the primary PCI, a successful coronary artery bypass graft operation was performed. After 4 years, the patient remained without any symptoms of neurological problems.